WAYANG SEBAGAI MEDIA PENDIDIKAN KARAKTER (PERSPEKTIF DALANG PURWADI PURWACARITA) - Mukhlisin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
Wayang is the right medium to convey character education to children. The story of wayang is very interesting and the characters of the characters can be used as examples of human behavior. Embedding character through wayang is an effort to strengthen identity. by retelling wayang in the classroom, students or the younger generation are introduced, taught and instilled the noble values contained in it. The introduction of character education with a game approach will be more fun for students and easier for them to understand. And in the end, with regard to character education as a priority for national education in the future, the life of the nation and state will be stronger based on the values of its cultural roots. Like Dalang purwadi purwacarita about the characters: wayang semar, humble, not arrogant, honest, and still loving others. Wayang Gareng, with handicapped hands, crooked feet, crossed eyes, symbolizes creativity, that creates something, and is not perfect. Puppet petruk, depicted in a long form that symbolizes the thought that must be long in living human life, must think long (not grusa-grusu) and be patient. Wayang bagong, Bagong has a character who likes to joke even when facing very serious problems and has a presumptuous nature